Singapore Public Enterprise In The Marine Industry - Sikorski, Douglas (Asian Academy of Management (AAM), 1999)
Shipyards are the characteristic institution of what is termed the 'marine industry.' The marine industry in Singapore constitutes three major segments: shiprepair, shipbuilding and rigbuilding (refer to Table 1). For shiprepair, the main segment of the marine industry in Singapore, an important competitive advantage has been the country's strategic location along the tanker route between the Middle East and the East Asian countries. Further advantages for Singapore are deemed to be its low costs, high efficiency and labour productivity. Singapore still provided for 60% of the Asian shiprepair market in 1995, but new competitors to challenge Singapore's secure market position were anticipated from emerging industries in countries such as China or Vietnam. However, necessary infrastructure there is years away from creating real potential for a serious competitive threat.